Umbilical Cord Blood-Derived Cells Can Reconstruct Hematopoiesis in an Aplastic Anemia Animal Model - Zesong Chen; Chen Yang; Jiang Ji; Miao Chen; Bing Han (Wiley, 2024)
Objectives. To explore the efficacy and the mechanism of the umbilical cord-derived cells combined with cyclosporine A (CsA) in treating aplastic anemia (AA) in mice. Methods. Immune-mediated AA model mice were treated with CsA + UC mesenchymal stem cells (UC-MSC), CsA + umbilical cord blood regulatory T cells (UCB-Treg), UC-MSC, UCB-Treg, CsA alone, or blank control, respectively (n = 9 mice/group). CsA and the cell infusion was administered on d0. Routine peripheral blood testing was performed once weekly; bone marrow colony culture, bone marrow cell flow cytometry, peripheral blood T cell subsets, and serum inflammatory cytokines tests were performed on d14. Transcriptome sequencing was performed for cells from CsA + UC-MSC, CsA + UCB-Treg, and CsA groups to detect the possible related genes. Gene function cluster and signal pathway enrichment analysis were also performed. Results. Blank control mice died due to pancytopenia within 21 days, whereas mice in other groups survived for >28 days. On d14, the CsA + UC-MSC and CsA + UCB-Treg groups had higher white blood cell (WBC) counts than the other groups (p<0.05), along with higher burst-forming unit (BFU) and colony-forming unit-granulocyte, macrophage (CFU-GM) counts (p<0.01). The CsA + UC-MSC group had the highest BFU count (p<0.01). The CsA + UC-MSC and CsA + UCB-Treg groups exhibited the highest bone marrow CD34+ cell proportion (9.68% ± 1.35% and 8.17% ± 0.53%, respectively; p<0.01). Tumor necrosis factor (TNF)-α and interleukin (IL)-2 levels in the CsA + UC-MSC group (p<0.05) and TNF-α, interleukin-2, and interferon (INF)-γ levels in the CsA + UC-Treg group (p<0.01) were lower than those in the CsA group. Compared with CsA treatment, CsA + UC-MSC significantly downregulated the histone methylation pathway (p<0.05), whereas CsA + UCB-Treg significantly upregulated energy metabolism processes (p<0.05). Treatment with CsA + UC-MSC upregulated superoxide dismutase activity compared with CsA + UCB-Treg treatment. Conclusions. Adding UC-MSC or UCB-Treg to CsA markedly enhanced the reconstruction of hematopoiesis in AA mice, with UC-MSC eliciting greater efficiency than UCB-Treg. Accordingly, the addition of these cells could further improve immune abnormalities.